Chapter 26 Ageism in a Cross-Cultural Perspective: Reflections from the Research Field (2018)
In this chapter, we discuss the opportunities and challenges of researching ageism from a cross-cultural perspective. We discuss the complexity of exploring diverse ageist practices as performed in different parts of the world. We also reflect upon the socio-cultural backgrounds through which researchers filter the experiences of fieldwork and research on various enactments of ageism. The key tenet of our argument is that these two dimensions interact during the fieldwork to create unique frameworks that researchers apply in their studies. We confront our experiences of researching ageism in Japan, Poland, Sweden, and West Papua to explore the notion that the socio-cultural context matters to the following aspects of ageism: diversity of ageist practices, societal images of later life, and the researchers’ socio-cultural understandings of ageism. We explore the position of researchers who, on the one hand, apply the privileged perspective of a stranger to their fieldwork, and on the other hand, are deeply embedded in their own socio-cultural background, which affects their way of approaching later life and ageism. We conclude with a notion of establishing a “sense of touch” within the field and a discussion recognizing the potential changes that such an approach can bring to the ways we study ageism worldwide.